2018
DOI: 10.1177/1464420718764513
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic material damping characteristics of carbon nanotubes based functionally graded composite shell structures

Abstract: This work deals with the study of viscoelastic modeling and vibration analysis of functionally graded nanocomposite shell panels where carbon nanotubes are reinforced in the polymer matrix based on the functionally graded distributions of carbon nanotubes. Five types of grading of carbon nanotubes (such as UD, FGX, FGV, FGO, and FGΛ) in the thickness directions have been considered in order to investigate the vibration damping performance of such composite shell panels. A detailed mathematical formulation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Rafie [16] studied the vibration and damping properties of epoxy composites modified with pristine and amino-functionalized graphene nanoplatelets (GNPs) at four different nanofiller loadings. Swain [17,18] conducted viscoelastic modeling and vibration analysis on nanocomposite shell panels with different CNTs and presented a detailed mathematical formulation for the determination of viscoelastic properties. Pan [19] prepared single-walled carbon nanotubes (SWCNTs)/7075 aluminum matrix composites to investigate the effects of different SWNTs contents on the microstructure and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Rafie [16] studied the vibration and damping properties of epoxy composites modified with pristine and amino-functionalized graphene nanoplatelets (GNPs) at four different nanofiller loadings. Swain [17,18] conducted viscoelastic modeling and vibration analysis on nanocomposite shell panels with different CNTs and presented a detailed mathematical formulation for the determination of viscoelastic properties. Pan [19] prepared single-walled carbon nanotubes (SWCNTs)/7075 aluminum matrix composites to investigate the effects of different SWNTs contents on the microstructure and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…25 The effect of viscoelastic properties of CNT-reinforced shells was also presented. 26 Additionally, CNT can be orthogonally reinforced in circumferential and longitudinal axes of cylindrical shells which were proposed and investigated. 27,28 The effect of variable thickness on the vibration and stability behavior of CNT-reinforced structures was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Duncan et al [36] analyzed the effect of CNT aspect ratio and epoxide-terminated surface modification on the glass transition temperature (Tg) and loss modulus (E") of nanocomposites. Swain and Roy [37] showed that quick vibration mitigation was possible by adding carbon nanotubes into the 934 epoxy according to micromechanics principles. Hirane et al [38] further investigated the static and free vibration of sandwich plates with layerwise finite element method, and the results showed that the developed model is promising in the accuracy and fast rate of convergence.…”
Section: Introductionmentioning
confidence: 99%